IDENTIFIKASI STATUS REPRODUKSI SAPI AKSEPTOR (ISRA) PADA KELOMPOK TERNAK SETETES MADU DESA CAMPLONG II KECAMATAN FATULEU KABUPATEN KUPANG PROVINSI NUSA TENGGARA TIMUR - Tarsisius Considus Tophianong; Yohanes T. R. M. R. Simarmata; Heny Nitbani (Jurnal Media Tropika, 2021)
East Nusa Tenggara (NTT) is one of the centers for beef cattle in eastern Indonesia, it has large areas and supportive natural potential. On the other hand, at Setetes Madu cattle group, in Camplong Village II, Fatuleu sub-district, Kupang Regency, East Nusa Tenggara Province, farming management and animal health management still traditionally maintains without planning and recording, as well as cattle rearing practice. Several problems of cattle farming development at Setetes Madu cattle group are, (1) unknown or unidentified of the individual reproductive health status of acceptor cattle; (2) minimum knowledge of farmers about cattle reproductive management includes breeding management and recording. The approaches to solving the problems are, (1) identification of the Reproductive Status of Acceptor Cattle to determine individual cattle reproductive health status and treatment to a cattle with the reproductive disorder; (2) educating cattle’s breeder about planned, recorded, measurable, and periodically evaluated and continuously of reproductive management. Without good reproductive management, efficiency reproductive will not be achieved, whereas, without reproductive efficiency, productivity will not be achieved. Reproduction performance and cattle health are important to achieve optimization, reproductive efficiency, profitability, and sustainable cattle breeding.